Química y Farmacología de Physalis peruviana L. (''Aguaymanto'') - Lock, Olga (2005)
This review article covers the present knowledge on the chemistry and biological activities of Physalis peruviana L.A description of the chemical compounds reported in the scientific literature is included. The biological activities of the crude extracts and pure compounds are discussed.